Effective Java - Bloch, Joshua (Boston : Addison-Wesley, 2018)
"Each chapter of Effective Java, Third Edition, consists of several "items," each presented in the form of a short, stand-alone essay that provides specific advice, insight into Java platform subtleties, and updated code examples. The comprehensive descriptions and explanations for each item illuminate what to do, what not to do, and why. The third edition covers language and library features added in Java 7, 8, and 9, including the functional programming constructs that were added to its object-oriented roots. Many new items have been added, including a chapter devoted to lambdas and streams" --Publisher.
Introduction -- Creating and destroying objects -- Methods common to all objects -- Classes and interfaces -- Generics -- Enums and annotations --Lambdas and streams -- Methods -- General programming -- Exceptions -- Concurrency -- Serialization.
"Updated for Java 9"--Cover.
"Best practices for ... the Java Platform" --Cover.
Includes bibliographical references and index.
CSE
Karim International
Keywords: Java (Computer program language).; COMPUTERS / Programming / Object Oriented; Java (Computer program language).; Computer science